Desain Karakter untuk Buku Panduan Kesehatan Gigi dan Mulut Balita - Wahyuni Adellia Putri; Aris Sutejo; Sri Wulandari (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
The introduction and care of teeth and mouth from an early age is very important to do because there are still many children with a high frequency of cavities and a low level of handling. Parents play an important role in guiding, understanding, reminding, and creating conditions that are conducive for children to maintain good oral health. So, it is necessary to have educational media for parents, especially mothers, in the form of guidebooks that discuss the importance of maintaining children's oral health. However, interest in reading is still very low. Because there are still many books whose material is delivered by writing only. That is what causes readers to get tired and bored quickly. Therefore, a character design is needed that functions as a decoration to support the message to be conveyed so that it is interesting to read. The data collection technique used is by conducting interviews, questionnaires, observation, and literacy. And using descriptive qualitative data analysis techniques and TOWS Matrix. The main characters in this design are pediatric dentists and mouth doctors, made so that readers feel like they are talking or listening to information from dentists and mouth doctors directly. In addition to the main character, there are supporting characters, namely mothers and children under five years of age.